Precision Medicine - Shuman, Jill (MD Conference Express, 2015)
The goal of precision medicine is to tailor medical treatments for patients based on their personal characteristics and responses to a specific treatment. Genome-wide association studies and pharmacogenomics are tools that may help clinicians determine how best to treat patients, such as those with breast cancer, based on genetic factors and phenotype.